Analisis Waktu Peluruhan Dini dan Waktu Dengung pada Ruang Teater - Kiki Rezki Lestari; Andika Ahmad Triputranto (Radial : Jurnal Ilmiah Sains dan Rekayasa, 2023)
In the stage of acoustic measurement of the room, a review of the research object, namely the Salihara Black Box Theater, is required. The review is conducted to obtain the necessary materials for the planning of the data collection format, such as the condition of the room when empty, examining the materials composing the surface of the room walls, as well as re-measuring the dimensions of the room and its equipment. The measurement of the room dimensions is also necessary for the empirical calculation of the Sabine reverberation time and for reproducing a model of the research object room. Moreover, it is used to consider the determination of the measurement points later on. All parameters are measured within the frequency range of 125 Hz to 4,000 Hz and taken from the perspective of comparing each receiving point. For the reverberation time (T30), values ranging from 0.6 seconds to 0.99 seconds are obtained. For the early decay time (EDT), values ranging from 0.45 seconds to 0.94 seconds are obtained. For clarity (C80), values ranging from 1.66 dB to 11.24 dB are obtained. For definition (D50), values ranging from 38.09% to 84.1% are obtained.